2000
DOI: 10.3109/13697130009167598
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-specific quality-of-life satisfaction during the menopause in an Arabian Gulf country

Abstract: The present study showed that menopause-related symptoms in UAE women are fewer and of less severity than in Western women. The postmenopausal women, despite a continued decline in estrogen levels, reported few symptoms as part of a normal life stage, suggesting that they were able to cope with stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
48
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 19 publications
9
48
1
Order By: Relevance
“…Acknowledging that women in the study varied in ethnicity and this may explain part of the differences in knowledge [21], women that were considered highly educated were likely to acquire knowledge actively and paid more attention to their health. In our study, 85% of symptom suffers thought the symptoms were tolerable and should not be treated, which is a rate comparable to those of other studies conducted in Asian and Arabic populations [22,23]. …”
Section: Discussionsupporting
confidence: 72%
“…Acknowledging that women in the study varied in ethnicity and this may explain part of the differences in knowledge [21], women that were considered highly educated were likely to acquire knowledge actively and paid more attention to their health. In our study, 85% of symptom suffers thought the symptoms were tolerable and should not be treated, which is a rate comparable to those of other studies conducted in Asian and Arabic populations [22,23]. …”
Section: Discussionsupporting
confidence: 72%
“…In a study which was done in UAE, 69% of the women reported physical symptoms, 58.7% reported psychosocial symptoms, 40% reported vasomotor symptoms and 37.9% reported sexual symptoms [19]. A study which was done by Sudhaa et al, showed that the mean number of postmenopausal symptoms were significantly higher in the > 50 years age group as compared to those in the ≤ 50 years age group [20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians and health policymakers are recognizing this pain as an important public health threat because of its negative impact on the individual and society 5,6 . Despite this impact, no studies have been conducted to date to analyze the quality of life related to foot health in women.…”
Section: Introductionmentioning
confidence: 99%